Management of Brine Disposal in Marine Environment: An Approach Towards Circular Economy in Qatar and other GCC countries - Hasa Abdullah (17679430) (2023)
The direct disposal of this brine into seawater impacts marine ecosystems due to its elevated salinity and temperature. This comprehensive review will explore the various desalination techniques employed in Qatar and other GCC countries of brine discharge on coral reefs. Additionally, this review paper will assess Qatar's current brine management strategies. Furthermore, the study aims to facilitate and propose sustainable brine solutions utilizing the DPSIR framework. It will also outline a circular economy approach to brine management in Qatar, evaluating its contribution to achieving the Sustainable Development Goals (SDG) targets such as SDG.6, SDG.7, and SDG.14 through sustainable brine management.